Late intermediate occupation at Cerro Azul, Perú : a preliminary report - Marcus, Joyce (Technical reports (University of Michigan. Museum of Anthropology), 1987)
Cerro Azul was a late prehistoric fishing community on the south-central coast of Peru. It was one of several communities that belonged to the region of Huarco before falling to the Inca. This volume is the preliminary report of an interdisciplinary project carried out at the site from 1982 to 1986. The remains of many buildings exist on the site. During this project, crews excavated four of these, as well as middens and burials.